Development and sensitivity analysis of MWCNTs coated D-shaped plastic optical fiber sensor for the detection of mercury - Khan, Abdul Ali; Thirunavakkarasu, Punithavathi M.; Muhammad Noor, Ahmad Shukri; Saidin, Norazlina; Waqas, Nawaf (Elsevier, 2024)
Heavy metal pollutants in rivers and water catchments are one of the problems faced by many developing countries as they may result in health issues among their people. A proper sensing mechanism is required to ensure the quality of water. In this research, we propose a simple, low cost, and highly sensitive D-shaped plastic optical fiber (POF) sensor layered with functionalized multi-walled carbon nanotubes (MWCNTs) for the detection of mercury in water. The sensor underwent interrogation across a range of mercury concentrations at room temperature. Numerous methods of characterization have been employed to explore the intricate structural attributes of the sensing layer to verify that the nanocomposite surface layer is functionalized with minimal disruption to the nanotubes. The experimental results revealed that the coated sensor displayed swift response and recovery time of 6.3 s and 13 s respectively when tested with the dynamic mercury concentration range (0 to 5 ppm). Moreover, it exhibited a relative absorbance of 7.33 %/ppm, which is approximately four times higher than the plain sensor and a limit of detection (LOD) of 0.1 ppm. The sensor has the potential to be transformed into an on-site, portable, real-time optical sensor for the detection of mercury ions in drinking water, offering high sensitivity and fast data acquisition.